PENINGKATAN PRESTASI BELAJAR SISWA MELALUI PEMBELAJARAN PORTOFOLIO PADA MATA PELAJARAN PRAKARYA DAN KEWIRAUSAHAAN KELAS XI AP 1 SMK PGRI LUMAJANG - Erna Susyowatiningsih (FKIP Universitas Islam Jember, 2015)
This study aims at investigating how the application of portfolio learning on student achievement in grade XI AP 1 SMK PGRI Lumajang on the subject of “Prakarya” and “Kewirausahaandan perusahaan dagang ”. The sample is the XI graders of SMK PGRI AP 1 Lumajang. The rtesearch design of this study was classroom action research (PTK). In the first cycle, the test results demonstrate knowledge minimum score of 1,4 and an average value of 2,74 of a maximum value of 3,8. Portfolio assessment results indicate a minimum value of 1,25 and an average value of 1,99 and a maximum value of 2,50. By observing learning completeness criteria of 2,67, the completeness of the knowledge value of 59%, but the value of nothing thorough skills. Results show the student's ability completeness 0%. In the second cycle, the knowledge test results showed the minimum value of 2,2 and an average value of 3,24 and a maximum value of a portfolio assessment 4. Results showed a minimum value of 2,50 and an average value of 3,01 and a maximum value of 3,75. By observing learning completeness criteria of 2,67, the completeness of the knowledge value of 97%, but the value of skill mastery by 90%. Results of the students there were thorough knowledge but skills are not complete, so the thoroughness of a total of 87%. This indicated that the cycle in this study can be stopped. It is therefore that it can be concluded that learning portfolio on the subject of “Prakarya” and “Kewirausahaandan perusahaan dagang” can be very practical and effective to improve the students’ achievement at Class XI AP 1 SMK PGRI Lumajang.Keywords : portfolio and learning achievement.